2019
DOI: 10.2147/dddt.s225264
|View full text |Cite
|
Sign up to set email alerts
|

<p>Memory Impairment Induced by Chronic Psychosocial Stress Is Prevented by L-Carnitine</p>

Abstract: Introduction: Psychosocial stress (STS) negatively influences memory. This might be associated to oxidative stress-induced progressive destruction of numerous brain structures and functions. L-carnitine (L-CAR) is a widely used antioxidant compound that is endogenously made in mammalian species. The current study investigated the effect of L-CAR on STS-induced memory impairment in the rat hippocampus. Methods: The STS was induced using intruder model, where two rats were randomly switched from each one cage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…), respectively, five times per week for three weeks. Doses of L-carnitine were selected according to previous studies (Rababa'h et al 2019;Jamali-Raeufy et al 2021). Group E received IV saline once weekly and L-carnitine at a dose of 300 mg/kg, i.p., five times per week for three weeks.…”
Section: Experimental Designmentioning
confidence: 99%
“…), respectively, five times per week for three weeks. Doses of L-carnitine were selected according to previous studies (Rababa'h et al 2019;Jamali-Raeufy et al 2021). Group E received IV saline once weekly and L-carnitine at a dose of 300 mg/kg, i.p., five times per week for three weeks.…”
Section: Experimental Designmentioning
confidence: 99%
“…Today, neuroprotective effects of L-carnitine administration have been reported in Parkinson’s disease (Burks et al, 2019), autism spectrum disorders (ASD) (Malaguarnera and Cauli, 2019), and Alzheimer’s disease (Kepka et al, 2020). It is also reported that daily administration of acetyl-L-carnitine at a dose of 300 mg/kg for 6 weeks improved memory loss and learning owing to mental stress in rats in the radial maze through increasing levels of the antioxidant enzymes glutathione reductase, catalase, and glutathione peroxidase (Rababah et al, 2019). However, in humans, L-carnitine consumption at 100 and 200 mg/kg/day for 1–6 months may improve ASD symptoms, but side effects such as diarrhea have been reported at high doses (Malaguarnera and Cauli, 2019).…”
Section: Introductionmentioning
confidence: 99%